2014
DOI: 10.1186/1471-2407-14-147
|View full text |Cite
|
Sign up to set email alerts
|

Invasive neuroendocrine carcinoma of the breast: a population-based study from the surveillance, epidemiology and end results (SEER) database

Abstract: BackgroundNeuroendocrine carcinoma (NEC) of the breast is a rare type of carcinoma that has not been well studied or characterized. Of the limited number of studies reported in the literature, most are case reports. A few small retrospective series studies have been reported.MethodsWe reviewed data on 142 cases of mammary NEC recorded in the surveillance, epidemiology, and end results (SEER) database during 2003–2009 and evaluated disease incidence and patient age, sex, and race/ethnicity; clinicopathologic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
158
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(170 citation statements)
references
References 10 publications
7
158
3
2
Order By: Relevance
“…NECs of the breast are usually seen in mature women, around the seventh or eighth decade of life, and the tumors tend to be larger (measuring ≥20 mm in diameter), higher grade, and more advanced than usual breast cancers. Studies have found both progression free survival and overall survival to be shorter than those of patients with usual IDC [7] [8]. However, in the present study, the patients with NEC had survival rates similar to those of patients with usual IDC and had favorable outcomes (MST of 75 months).…”
Section: Discussioncontrasting
confidence: 52%
“…NECs of the breast are usually seen in mature women, around the seventh or eighth decade of life, and the tumors tend to be larger (measuring ≥20 mm in diameter), higher grade, and more advanced than usual breast cancers. Studies have found both progression free survival and overall survival to be shorter than those of patients with usual IDC [7] [8]. However, in the present study, the patients with NEC had survival rates similar to those of patients with usual IDC and had favorable outcomes (MST of 75 months).…”
Section: Discussioncontrasting
confidence: 52%
“…Sporadically, NECB may lead to clinical conditions related to hormonal hypersecretion, because of ectopic production of adrenocorticotropic hormone [20], norepinephrine [21], or calcitonin [22]. The disease is more commonly diagnosed in elderly women in their sixth or seventh decade of life [3]. Only a few cases of NECB have been reported in males [3,23,24].…”
Section: Clinical Presentation and Diagnostic Work-upmentioning
confidence: 99%
“…The disease is more commonly diagnosed in elderly women in their sixth or seventh decade of life [3]. Only a few cases of NECB have been reported in males [3,23,24].…”
Section: Clinical Presentation and Diagnostic Work-upmentioning
confidence: 99%
See 2 more Smart Citations